Fluid Identities and Social Disruption: A Critical Examination of Otherness in the Íslendingaþættir - Solveig Bollig (Nordlit: Tidsskrift i litteratur og kultur)
This article explores the concept of Otherness in two íslendingaþættir: Þórhalls þáttr knapps and Auðunar þáttr vestfirska. By analysing the protagonists’ social behaviour and interactions within the context of societal and situational shifts, this study examines how Otherness is constructed, challenged, and renegotiated throughout the narratives. Employing a framework of fluid and positive Otherness, this study examines how Othering qualities can be diminished or cemented as a result of individual behaviour and societal reactions. This approach underscores the importance of examining Otherness as a context-sensitive concept, with Otherness being both a source of disruption and a potential means for social reintegration.